THE STRATEGY OF THE LIBRARY AND ACCOUNTABILITY OF PANGANDARAN DISTRICT IN INCREASING COMMUNITY READING INTEREST - Restiani; Endah Vestikowati; Asep Nurwanda (JGSRD: Journal of Government Science and Rural Development, 2020)
This research is motivated by the lack of the strategy of the Pangandaran Regency Library and Archives Service in increasing people's interest in reading. The research method used is descriptive qualitative. The length of the research that the author did was 9th months. The data collection techniques through observation, interviews, documentation. The number of informants was 12 people. Data collection techniques through data reduction, data presentation, concluding, or verification. Based on the results of the study, it can be concluded that: first, the implementation of strategies in increasing people's reading interest by the Department of Library and Archives of Pangandaran Regency has been running optimally. Second, there are obstacles such as the still small budget or funds in library management, especially for the provision of library facilities so that the library development program to attract public reading interest has not been achieved properly, this is based on the lack of facilities and infrastructure to succeed the planned strategy. Previously with the condition of employees who did not have an understanding of the field of libraries, so that the service was not optimal for users. Third, efforts are made, namely asking for additional budget assistance from both the Regency and Provincial Governments to complete the procurement of complete library facilities along with the fulfillment of the budget for library development programs and for efforts to provide employee resources who understand the library sector, guidance is carried out for library staff regarding the library sector. and staff are included in basic library management training.